Tāḥlīl Kitāb TOAFL “Muqārrār Tāḥdīd āl-Mustāwā” āl-Mustānīdī īlā āl-Iṭār āl-Ūrūbī āl-Mārjāʿī āl-Mushtārāk līl-Lughāt - Syarofit, Miqdarul Khoir; Mahliatussikah, Hanik; Alfan, Muhammad; Abushihab, Eiman F. (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The rising demand for standardized Arabic language proficiency tests, especially for international institutions like Al-Azhar University in Egypt, underscores the need to evaluate current assessment tools for validity and global alignment. This study analyzes the TOAFL Muqarrar Taḥdīd Mustawā textbook using the Common European Framework of Reference for Languages (CEFR) to assess its suitability for testing the language skills of prospective students of Al-Azhar University in Egypt. Employing a descriptive qualitative method with quantitative data estimation, the study examined the number of questions, their distribution across language skills (listening, reading, writing, grammar), difficulty levels, and CEFR classification (A1–C2). Findings show that most items are concentrated at the intermediate levels (B1–B2), with limited coverage of advanced levels (C1–C2). Additionally, the distribution of skills is uneven, and questions lack integration within realistic contexts. The study recommends enhancing content diversity, incorporating higher-order thinking and critical reasoning tasks, and improving the integration of skills to align more closely with CEFR standards. This research offers a structured evaluation model for Arabic language testing materials, providing a systematic approach to analyze test content and language proficiency alignment. The study recommends aligning local Arabic language assessments with international frameworks, such as the CEFR, to enhance students’ academic readiness and competitiveness in global academic contexts.